Symposium 2: The social construction of educational technology through the use of proprietary software - Bissell, Chris (Proceedings of the International Conference on Networked Learning, 2010)
Major strands of science and technology studies (STS) in recent decades have been the ‘social shaping of technology’ (SST) and ‘social construction of technology’ (SCOT) movements, whose adherents maintain that technological systems are determined just as much by social forces as by technological ones. Taking this ‘co-construction’ notion as a starting point, and putting a focus on the user, I look at some examples of the use of proprietary software in which the learner, instead of being constrained by a rather deterministic pedagogy of educational technology, can exploit the functionality of the software in ways far removed from the original design. For example, spreadsheets can be used to incorporate modelling assumptions directly to simulate digital signal transmission, or the workings of the binomial function. Audio editing software can be used to teach about the technology of music by allowing the student to explore waveform characteristics. The manipulation of images, if combined with a teaching of the principles behind data compression, can engender a deep understanding of the processes involved. And translation software can be used for language learning in a way very different from what was envisaged by the designers. Educational technology has tended to suffer from an emphasis on, and excessive claims for, technological innovation and novelty. Film, radio, television, programmed learning, interactive video discs, CD-ROMs, a ‘computer in every classroom’, ‘one laptop per child’, the web, computer-mediated communication, smartboards; and now mashups, Second Life, Facebook, YouTube and Twitter – all have all been seen as radical new technologies that would revolutionize learning. Here I make the case for the social construction of educational technology by users and teachers, based on exploiting to far better effect the possibilities of mature, often proprietary, software not originally designed for pedagogical purposes. The approach outlined here not only helps students gain experience with the sort of software they are likely to encounter in their professional life, but also fosters and sustains a healthy spirit of enquiry that too often is lacking in much educational software. Although the examples presented have been situated in the context of the individual learner, similar principles can be applied to a whole range of networked educational technologies.